Cost of provision of opioid substitution therapy provision in Tijuana, Mexico - Burgos, Jose Luis (Harm Reduct J, 2018)
BACKGROUND: Mexico recently enacted drug policy reform to decriminalize possession of small amounts of illicit drugs and mandated that police refer identified substance users to drug treatment. However, the economic implications of drug treatment expansion are uncertain. We estimated the costs of opioid substitution therapy (OST) provision in Tijuana, Mexico, where opioid use and HIV are major public health concerns. METHODS: We adopted an economic health care provider perspective and applied an ingredients-based micro-costing approach to quantify the average monthly cost of OST (methadone maintenance) provision at two providers (one private and one public) in Tijuana, Mexico. Costs were divided by type of input (capital, recurrent personnel and non-personnel). We defined “delivery cost” as all costs except for the methadone and compared total cost by type of methadone (powdered form or capsule). Cost data were obtained from interviews with senior staff and review of expenditure reports. Service provision data were obtained from activity logs and senior staff interviews. Outcomes were cost per OST contact and cost per person month of OST. We additionally collected information on patient charges for OST provision from published rates. RESULTS: The total cost per OST contact at the private and public sites was $3.12 and $5.90, respectively, corresponding to $95 and $179 per person month of OST. The costs of methadone delivery per OST contact were similar at both sites ($2.78 private and $3.46 public). However, cost of the methadone itself varied substantially ($0.34 per 80 mg dose [powder] at the private site and $2.44 per dose [capsule] at the public site). Patients were charged $1.93–$2.66 per methadone dose. CONCLUSIONS: The cost of OST provision in Mexico is consistent with other upper-middle income settings. However, evidenced-based (OST) drug treatment facilities in Mexico are still unaffordable to most people who inject drugs.